2021
DOI: 10.3390/ma14226941
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Growth of Hydroxyapatite on SiO2 Microspheres to Improve Its Biocompatibility and Gentamicin Loading Capacity

Abstract: The interest in multifunctional biomaterials to be implanted are also able to release drugs that reduce pain and inflammation or prevent a possible infection has increased. Bioactive materials such as silica (SiO2) containing surface silanol groups contribute to the nucleation and growth of hydroxyapatite (HAp) in a physiological environment. Regarding biocompatibility, the spherical shape of particles is the desirable one, since it does not cause mechanical damage to the cell membrane. In this work, the synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…The results are expressed as the hemolytic ratio, labelled in three categories, with <2% indicating non-hemolytic, 2–5% slightly non-hemolytic, and >5% hemolytic. In our study, the observations were in agreement with previously reported results [ 41 , 49 , 50 ]. A maximum hemolysis value of 3.66% in Sample 2 showed increased thrombogenicity, which may be the result of greater blood–surface interactions due to the ionic groups in Si-HA interacting with certain blood components ( Table 4 ) [ 51 ].…”
Section: Resultssupporting
confidence: 94%
“…The results are expressed as the hemolytic ratio, labelled in three categories, with <2% indicating non-hemolytic, 2–5% slightly non-hemolytic, and >5% hemolytic. In our study, the observations were in agreement with previously reported results [ 41 , 49 , 50 ]. A maximum hemolysis value of 3.66% in Sample 2 showed increased thrombogenicity, which may be the result of greater blood–surface interactions due to the ionic groups in Si-HA interacting with certain blood components ( Table 4 ) [ 51 ].…”
Section: Resultssupporting
confidence: 94%
“…As the surface of SiO 2 contains silanol groups, it is conducive to the nucleation and growth of HAP on the surface of SiO 2 in the physiological environment. 96 The results conrmed that SiO 2 /HAP samples had better biocompatibility and drug loading ability in vitro than SiO 2 samples. Adding a biocompatible HAP microsheet layer to the TiO 2 /polymer hybrid layer, can produce a loose lm structure and enhance the photocatalytic surface, which can help kill more microorganisms and improve the antibacterial performance.…”
Section: Recombination Of Hap-based Carriersmentioning
confidence: 95%